Feasibility and therapeutic efficacy of a two-week low-level laser acupuncture therapy for shoulder and neck pain in office workers: Protocol for a pilot, single-blind, double-armed, randomised controlled trial. - Carol Chunfeng Wang; Lisa Whitehead; Travis Cruickshank; Johnny Lo; Jianhong Cecilia Xia; Jun Wen (PLoS ONE)
Background Shoulder and neck pain (SNP) is common in office workers and represents a serious public health problem given its detrimental impact on quality of life, physical functioning, personal finances, employers, and the health care system. Management with painkillers has adverse implications such as tolerance, addiction, and opioid abuse. Safe, sustainable, cost-effective, and evidence-based solutions are urgently needed. The non-invasive, painless, non-infectious, and safe modality of low-level laser acupuncture (LLLA) has shown promise for SNP management. Objective The overarching aim of this study is to provide evidence of the feasibility and therapeutic efficacy of LLLA for office workers with SNP. Methods This is a pilot, single-blind, double-armed, randomised controlled trial on the feasibility and therapeutic efficacy of a two-week LLLA therapy for office workers with SNP, aged 18 to 65 years. Each of the two study groups will contain 35 participants: the intervention group will receive LLLA from a licensed acupuncturist at the researchers' university clinic (10-20 min/session, 3 sessions/week) for two weeks; the control group will receive usual care without painkillers. Outcomes will be measured at baseline, throughout the two-week intervention, and at trial end. Surveys including open-ended questions will be completed. The primary outcome of this study is to evaluate the feasibility of a two-week LLLA therapy for office workers with SNP, as measured by recruitment and completion rates, patient safety, and treatment adherence and compliance. Participants' attitudes, motivation, and challenges to participation, intervention non-compliance, and experience of participating in the trial will be investigated via qualitative data. The secondary outcome is to evaluate the therapeutic efficacy of LLLA on SNP using the visual analogue scale (VAS) and the Short-Form McGill Pain Questionnaire (SF-MPQ); the work productivity and activity assessment (WPAI:SHP); 12-Item Short Form Survey (SF-12) for quality of life assessment; and the past 3-month out-of-pocket (OOP) cost for prescription and non-prescription SNP therapy, which is an indicative of the economic burden of SNP on patients and health care systems. This study was approved by Edith Cowan University's Human Research Ethics Committee (No. 2021-02225-WANG). Results Data collection will commence in December 2021 with anticipated completion by December 2022. Conclusions Safe, sustainable, cost-effective, evidence-based interventions are needed to minimise the negative implications of SNP in office workers. LLLA is a promising modality in managing SNP. However, more consolidated evidence is required to provide insight regarding the effectiveness of LLLA. This study is expected to contribute to the challenging work of reducing the burden of SNP in office workers. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12621000426886p; https://www.anzctr.org.au/ACTRN12621000426886p.aspx.